CCM-AMI, a Polyethylene Glycol Micelle with Amifostine, as an Acute Radiation Syndrome Protectant in C57BL/6 Mice. Issue 3 (September 2015) - Chen, Chia-Hung; Kuo, Min-Liang; Wang, Jen-Ling; Liao, Wei-Chuan; Chang, Li-Ching; Chan, Leong-Perng; Lin, Johnson
Abstract : Abstract: Acute radiation syndrome results from radiation exposure, such as in accidental nuclear disasters. Safe and effective radioprotectants, mitigators, and treatment drugs must be developed as medical countermeasures against radiation exposure. Here, the authors evaluated CCM-Ami, a novel polyethylene glycol micelle encapsulated with amifostine, for its radioprotective properties after total-body irradiation from a 60 Co source. Male C57BL/6 mice (6–8 wk old) were intravenously injected with 45 mg kg −1 of CCM-Ami 90 min before exposure to 7.2 and 8.5 Gy irradiation at a dose rate of 0.04 Gy min −1 . Both survival benefit and hematopoietic protection were observed after prophylactic CCM-Ami administration when compared with the effects measured in excipient control and amifostine groups. Pharmacokinetic results showed that after the intravenous injection, the plasma concentration of WR‐1065, the active form of amifostine, was higher in CCM-Ami-treated mice than in amifostine-treated mice. These findings suggest that CCM-Ami-mediated hematopoietic protection plays a key role in enhancing survival of mice exposed to radiation toxicity and thus indicate that CCM-Ami is a radioprotectant that can be used safely and effectively in nuclear disasters.